2012
DOI: 10.1371/journal.pone.0050032
|View full text |Cite
|
Sign up to set email alerts
|

Can Multiple Lifestyle Behaviours Be Improved in People with Familial Hypercholesterolemia? Results of a Parallel Randomised Controlled Trial

Abstract: ObjectiveTo evaluate the efficacy of an individualised tailored lifestyle intervention on physical activity, dietary intake, smoking and compliance to statin therapy in people with Familial Hypercholesterolemia (FH).MethodsAdults with FH (n = 340) were randomly assigned to a usual care control group or an intervention group. The intervention consisted of web-based tailored lifestyle advice and face-to-face counselling. Physical activity, fat, fruit and vegetable intake, smoking and compliance to statin therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 54 publications
1
59
1
Order By: Relevance
“…The Medication Adherence Report Scale (MARS-5) was selected for medication adherence. The MARS-5 questionnaire has been employed before in FH research and validity as well as reliability of MARS-5 has been found acceptable [14,15]. MARS-5 contains questions about e.g.…”
Section: Medication Adherencementioning
confidence: 99%
“…The Medication Adherence Report Scale (MARS-5) was selected for medication adherence. The MARS-5 questionnaire has been employed before in FH research and validity as well as reliability of MARS-5 has been found acceptable [14,15]. MARS-5 contains questions about e.g.…”
Section: Medication Adherencementioning
confidence: 99%
“…Cohort data facilitated epidemiological and causal inference studies for modifiable risk factors (e.g., smoking) [19-22]. Mortality data and mimicking a hard endpoint trial in follow-up data persuaded insurance companies to provide average premiums for identified and treated mutation-positive individuals [23-25].…”
Section: Aim 1: Assessing the Challenges And Opportunities Of Implemementioning
confidence: 99%
“…and lifestyle factors such as diet, phenotypic measures, physical activity (26)(27)(28)(29) and composite lifestyle score changes (30) . In an intervention which targeted both changes in physical activity and dietary intakes, the investigators reported that a tailored programme resulted in more significant lifestyle changes including increases in physical activity levels, decreases in fat and increases in fruit and vegetables intake (26) .…”
Section: Personalised Nutrition -How Effective Is It?mentioning
confidence: 99%